2004
DOI: 10.1136/jcp.2003.012658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the polymerase chain reaction for the rapid diagnosis of tuberculosis

Abstract: Aims: Use of the polymerase chain reaction for the detection of Mycobacterium tuberculosis (TB PCR) as a basis for making clinical decisions on the initiation of antituberculosis treatment was studied. Methods: A retrospective study involving a cohort of 155 patients being investigated for tuberculosis in an infectious disease consultation service was undertaken. TB PCR was performed on pulmonary and extrapulmonary specimens from these patients. The sensitivity of TB PCR was analysed. Results: Of the 155 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 18 publications
4
74
0
3
Order By: Relevance
“…55-75%: Haas et al 2000;Zink et al 2001a;Fletcher et al 2003;Zink et al 2003). These latter data compare favourably with published rates of detection using simple PCR-based systems on modern, diagnosed, clinical samples, which are around 80% (Portillo-Gomez et al 2000;Van der Spoel van Dijk et al 2000;Mitarai et al 2001;Narayanan et al 2001;Alfonso et al 2002;Yee et al 2002;Leung et al 2003;Cheng et al 2004), and higher than detection rates for blood (40%: Taci et al 2003), urine (56%: Kafwabulula et al 2002), and host DNA in studies of animal bones from temperate archaeological sites (around 10-20%: Haynes et al 2002;Edwards et al 2004). The high frequency of amplification success from archaeological samples has been attributed to the enhanced stability of the M. tuberculosis cell wall (Donoghue et al 2004).…”
Section: (Tpp15-l171 (Gcgttctgcccttttgacgttg)/h86 (Ccgactgctcagcccactsupporting
confidence: 76%
“…55-75%: Haas et al 2000;Zink et al 2001a;Fletcher et al 2003;Zink et al 2003). These latter data compare favourably with published rates of detection using simple PCR-based systems on modern, diagnosed, clinical samples, which are around 80% (Portillo-Gomez et al 2000;Van der Spoel van Dijk et al 2000;Mitarai et al 2001;Narayanan et al 2001;Alfonso et al 2002;Yee et al 2002;Leung et al 2003;Cheng et al 2004), and higher than detection rates for blood (40%: Taci et al 2003), urine (56%: Kafwabulula et al 2002), and host DNA in studies of animal bones from temperate archaeological sites (around 10-20%: Haynes et al 2002;Edwards et al 2004). The high frequency of amplification success from archaeological samples has been attributed to the enhanced stability of the M. tuberculosis cell wall (Donoghue et al 2004).…”
Section: (Tpp15-l171 (Gcgttctgcccttttgacgttg)/h86 (Ccgactgctcagcccactsupporting
confidence: 76%
“…Most extrapulmonary specimens do not have a large concentration of bacilli. In addition, the culture of M. tuberculosis is time consuming, taking 6-8 weeks for the growth to appear [5]. So, mostly, the diagnosis of tuberculosis depends on histological evidence, which may also sometimes be inconclusive, in addition to the need for high levels of expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional microbiological methods like Ziehl-Neelson staining (Z-N smear) for acid fast bacilli (AFB) and culture of Mycobacterium tuberculosis on Lowenstein Jensen media (L-J) have much lower sensitivity and specificity because of the paucibacillary nature of extrapulmonary tuberculosis [10,24]. Also, for a positive AFB smear, 5,000-10,000 bacilli per mL are needed [5]. Most extrapulmonary specimens do not have a large concentration of bacilli.…”
Section: Introductionmentioning
confidence: 99%
“…19 Various studies observed the results of PCR technique to diagnose extrapulmonary TB. 8,20 Currently, various PCR studies have developed into GeneXpert MTB/RIF method using heminested real-time polymerase chain reaction (PCR) assay. 11,17,21 This system works automatically toward the lysis of bacteria, extraction of the DNA, amplifications, and the detection of amplicon in a single system using a rapid approach.…”
Section: Discussionmentioning
confidence: 99%